Memorializing the Holocaust : gender, genocide and collective memory - Jacobs, Janet Liebman (I. B. Tauris, 2010)
How do collective memories of histories of violence and trauma in war and genocide come to be created? Janet Jacobs offers new understandings of this crucial issue in her examination of the representation of gender in the memorial culture of holocaust monuments and museums